Meyerhold's theater and biomechanics - Contemporary Arts Media (Australia : Contemporary Arts Media, 1999)
Russian actor and pedagogue, Gennadi Bogdanov, presents the most important etudes and principles of Meyerhold's Biomechanics. Includes archival photographs and film of Meyerhold's original work and also recent scenic work from Europe and the U.S. developed on the principles of biomechanics.
DVD format
Keywords: Meierkhold, V. E -- 1874-1940 -- Criticism and interpretation; Eisenstein, Sergei, -- 1898-1948 -- Criticism and interpretation; Theater -- Soviet Union -- History -- 20th century; Experimental theater -- 20th century; Movement (Acting)